Utilization of Nanocellulose from Red Onion Skins as Nanofiller in Polyvinyl Alcohol-Based Film - Laila Rezty Hertiwi; Mukhamad Rojib Aminudin; I Gusti Made Sanjaya (Jurnal Kimia Sains dan Aplikasi, 2024)
Research has been conducted to apply nanocellulose from red onion skins as a nanofiller on polyvinyl alcohol (PVA) based films. It aims to determine the effect of red onion skin nanocellulose on PVA-based films in improving mechanical and biodegradation properties. Nanocellulose was produced from the skin of red onions through an acid hydrolysis process with a temperature of 45°C for 40 minutes. The resulting nanocellulose was characterized using FTIR, XRD, and SEM. Nanocellulose, with concentrations of 10%, 20%, 30%, 40%, and 50%, was then used as a filler in PVA-based films. The results were characterized to determine the mechanical and biodegradation properties. The nanocellulose obtained from the red onion skins in this study was 12.615 nm with a crystallinity index of 78.668%. The optimum tensile strength was achieved at 14.7573 MPa in PVA-based film filled with 20% nanocellulose extracted from red onion skins. The greatest elongation percentage of 118.3265% was observed in a PVA-based film containing 50% nanocellulose from red onion skins. Moreover, optimal biodegradation occurred in PVA films incorporating 50% nanocellulose from red onion skins, resulting in a weight loss of 12.86% over 14 days.